1999
DOI: 10.1107/s0907444998011901
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of a non-natural amino acid (aza-tryptophan) may help to crystallize a protein and to solve its crystal structure. Application to bacteriophage λ lysozyme.

Abstract: Until now, wild-type bacteriophage λ lysozyme had been impossible to crystallize. This difficulty could be overcome by the replacement of the four tryptophan residues by aza-tryptophans. Analysis of the intermolecular and intramolecular contacts in this modification allows understanding of the differences in behaviour between the native and modified molecules. Furthermore, this mutation was very useful for the creation of new heavy-atom binding sites and for the solution of the non-crystallographic symmetry, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…While 7AT has been used effectively in situations where biological activity is retained, the rates of activity changed significantly upon substitution. Another indication of the significant differences 7AT-substitution introduces into biological environments is the experimental finding that certain 7AT-substituted proteins can be crystallized, where the corresponding nonmutant tryptophan-containing proteins have not been crystallized . It appears that the presence of the ring-bound N at the 7-position in 7AT plays an important structural as well as spectroscopic role in determining the properties of this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…While 7AT has been used effectively in situations where biological activity is retained, the rates of activity changed significantly upon substitution. Another indication of the significant differences 7AT-substitution introduces into biological environments is the experimental finding that certain 7AT-substituted proteins can be crystallized, where the corresponding nonmutant tryptophan-containing proteins have not been crystallized . It appears that the presence of the ring-bound N at the 7-position in 7AT plays an important structural as well as spectroscopic role in determining the properties of this molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Difficulties in the preparation of suitably diffracting crystals of wild-type LaL have been noted by Evrard and co-workers, and led to the finding that the replacement of Trp residues with 7-azatryptophan residues in this protein allowed for the formation of suitably diffracting crystals (30,31). It has been suggested that the incorporation of this unnatural amino acid may have resulted in additional hydrogen bonding interactions that could have contributed to the formation of these crystals (31). In our own hands, many attempts to produce suitably diffracting crystals of the wild-type LaL also met with failure.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have helped elucidate the molecular interactions between the oligosaccharide and enzyme, and have helped to define the number and location of each saccharide subsite in each lytic transglycosylase. Although the determination of the crystal structure of the bacteriophage lambda lytic transglycosylase has remained enigmatic, a derivative of LaL (mLaL for modified LaL) wherein all tryptophan residues have been replaced with 7-azatryptophan has allowed for the formation of crystals suitable for successful structure determination ( , ). However, to date, no structure has been determined for a cocrystal of LaL with a saccharide, preventing the elucidation of the exact nature of the saccharide−protein interaction for this phage lytic transglycosylase and of the detailed conformational changes that occur in LaL upon saccharide binding.…”
mentioning
confidence: 99%